LITERATURE REVIEW ON THE DOUBLE-EDGED SWORD OF AI IN MENTAL HEALTH: A DEEP DIVE INTO CHATGPT'S CAPABILITIES AND LIMITATIONS - Arjanto, Paul; Senduk, Feibry Feronika Wiwenly (Journal of Community Mental Health and Public Policy, 2024)
Background: This paper focuses on the increasing relevance of AI in mental health care, particularly OpenAI's ChatGPT. It investigates the changing dynamics in mental health, analyzing ChatGPT's role, its benefits, drawbacks, and ethical complexities. Purpose: The objective is to assess ChatGPT's effectiveness in mental health, highlighting its strengths and limitations, and ethical issues. The study aims to understand how AI support can be balanced with the vital human aspect in mental health care. Methods: Comprehensive literature review of 7 pieces of literature from the Scopus database in 2023 (latest). Results: ChatGPT is found to be a useful initial mental health support tool, offering immediate access. However, it falls short in delivering the emotional depth that human health professionals provide. Key ethical concerns include data privacy and accountability. Conclusion: The study recommends a balanced approach, suggesting ChatGPT as an adjunct rather than a replacement for conventional mental health services. Effective use of ChatGPT in mental health care requires strict ethical guidelines and control measures to maintain the crucial human element in this field. Abstrak Latar Belakang: Artikel ini berfokus pada meningkatnya relevansi AI dalam layanan kesehatan mental, khususnya ChatGPT OpenAI. Laporan ini menyelidiki dinamika perubahan dalam kesehatan mental, menganalisis peran ChatGPT, manfaat, kelemahan, dan kompleksitas etikanya. Tujuan: Tujuannya adalah untuk menilai efektivitas ChatGPT dalam kesehatan mental, menyoroti kekuatan dan keterbatasannya, serta masalah etika. Studi ini bertujuan untuk memahami bagaimana dukungan AI dapat diseimbangkan dengan aspek vital manusia dalam perawatan kesehatan mental. Metode: Tinjauan pustaka yang menyeluruh terhadap 7 literatur dari database Scopus pada tahun 2023 (terbaru). Hasil: ChatGPT terbukti menjadi alat dukungan kesehatan mental awal yang berguna, menawarkan akses langsung. Namun, hal ini gagal dalam memberikan kedalaman emosional yang diberikan oleh para profesional kesehatan manusia. Masalah etika utama mencakup privasi dan akuntabilitas data. Kesimpulan: Studi ini merekomendasikan pendekatan yang seimbang, menyarankan ChatGPT sebagai tambahan dan bukan pengganti layanan kesehatan mental konvensional. Penggunaan ChatGPT yang efektif dalam perawatan kesehatan mental memerlukan pedoman etika yang ketat dan tindakan pengendalian untuk mempertahankan elemen manusia yang penting dalam bidang ini.